THE DETAILED RECORD OF CLIMATIC EVENTS DURING THE PAST 75,000 YRS BP FROM THE LAKE BAIKAL DRILL CORE BDP-93-2 - Prokopenko A.A.; Karabanov E.B.; Williams D.F.; Kuzmin M.I.; Gvozdkov A.A.; Khursevich G.K. (My University, 2001)
By correlating the pronounced interstadial-type diatom peak with MIS 3, the high-resolution and well-dated record BDP-93-2 from the Selenga Delta area of Lake Baikal complements the classical long paleoclimatic records from Academician Ridge, which lack the pronounced MIS 3 warm signal. This correlation helps to resolve the age model controversies related to this interstadial interval. The content and C/N ratios of total organic carbon, as well as its stable isotope composition and diatom abundance, reveal high-frequency oscillatory variations reflecting the more unstable conditions of MIS 3 interstadial in the Lake Baikal region as compared with the Holocene interglacial.An important part of the regional climatic instability during the past 75,000 yrs BP revealed for the first time in the Baikal record is the recurrence of the abrupt erosional events leading to the deposition of the detrital carbonate material at the hemipelagic BDP-93 site. There were at least five such events: at MIS 5/4 transition, in the middle of MIS 4, and three during MIS 3. Stratigraphic and AMS-radiocarbon age models allow the Baikal erosional carbonate events to be confidently correlated to the intervals of Heinrich layers in the North Atlantic. This correlation suggests a surprisingly strong climatic teleconnection of the remote mid-continent Baikal location with the Dansgaard–Oeschger events and the bond cycles in the North Atlantic region.
Keywords: Baikal; Holocene interglacial; Climatic teleconnection; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен